2013
DOI: 10.1371/journal.pgen.1003162
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Dynamics Elicited by a Short Pulse of Notch Activation Involves Feed-Forward Regulation by E(spl)/Hes Genes

Abstract: Dynamic activity of signaling pathways, such as Notch, is vital to achieve correct development and homeostasis. However, most studies assess output many hours or days after initiation of signaling, once the outcome has been consolidated. Here we analyze genome-wide changes in transcript levels, binding of the Notch pathway transcription factor, CSL [Suppressor of Hairless, Su(H), in Drosophila], and RNA Polymerase II (Pol II) immediately following a short pulse of Notch stimulation. A total of 154 genes showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 72 publications
6
72
0
Order By: Relevance
“…Indeed, at least one incoherent feedforward or feedback loop was present among the targets of each pathway, with the exception of Notch and Wnt. We note, however, that incoherent feedforward loops have previously been identified downstream of Notch in another cell type (13,14).…”
Section: Direct Transcriptional Regulation Of Pathway Components By Smentioning
confidence: 51%
See 2 more Smart Citations
“…Indeed, at least one incoherent feedforward or feedback loop was present among the targets of each pathway, with the exception of Notch and Wnt. We note, however, that incoherent feedforward loops have previously been identified downstream of Notch in another cell type (13,14).…”
Section: Direct Transcriptional Regulation Of Pathway Components By Smentioning
confidence: 51%
“…1C). In addition, these time points are likely optimal for detecting the expression of primary target genes (12,13,16,27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…terms highlighted in bold in Table 1 and Table S6 the correct development and growth of nerve tissue (Housden et al 2013). It was shown by (Gao et al 2013) that the…”
mentioning
confidence: 99%
“…Furthermore, the different signaling pathways are not only in an ON/OFF state, but there are also oscillatory feedback loops and intensity effects that determine their final outcome. Genomic studies in Drosophila have shown that Hes repressors are at the base of the oscillatory feedback loops observed in the Notch pathway [67], an observation that has been confirmed in several mammalian systems. In the embryonic aorta, when HSCs are formed, Notch signaling leads to the transcriptional activation of both Hes1 and the hematopoietic gene Gata2.…”
Section: Resultsmentioning
confidence: 79%